2020
DOI: 10.3389/fmicb.2020.00173
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Antidiabetic Monomers Combination Alleviates Insulin Resistance Through Bacteria-Cometabolism-Inflammation Responses

Abstract: The present study sought to examine the therapeutic effect of a novel antidiabetic monomer combination (AMC) in treating type 2 diabetes mellitus (T2DM); while also elucidating the potential functional mechanism. Male C57BL/6J mice were fed a highfat diet (HFD) for 12 weeks to establish T2DM. The AMC group showed significant reduction in weight, fasting blood glucose (FBG), serum total cholesterol (TC) and low density lipoprotein cholesterol (LDL-C), and experienced reduced insulin resistance based on oral glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…Based on Kyoto Encyclopedia of Genes and Genome prediction, the abundant functional annotations of cecal microbiota were those corresponding to carbohydrate metabolism, amino acid metabolism, membrane transport, replication and repair, energy metabolism, translation, poorly characterized, nucleotide metabolism, cellular processes and signaling, and metabolism of cofactors and vitamins. These predicted functions of cecal microbiota in broilers were similar to those predicted by other studies ( Ma et al., 2018 ; Hu et al., 2020 ). However, the addition of B. subtilis or zinc bacitracin had little effect on the predicted functions of cecal microflora in broilers.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Based on Kyoto Encyclopedia of Genes and Genome prediction, the abundant functional annotations of cecal microbiota were those corresponding to carbohydrate metabolism, amino acid metabolism, membrane transport, replication and repair, energy metabolism, translation, poorly characterized, nucleotide metabolism, cellular processes and signaling, and metabolism of cofactors and vitamins. These predicted functions of cecal microbiota in broilers were similar to those predicted by other studies ( Ma et al., 2018 ; Hu et al., 2020 ). However, the addition of B. subtilis or zinc bacitracin had little effect on the predicted functions of cecal microflora in broilers.…”
Section: Discussionsupporting
confidence: 89%
“… Salaheen et al. (2017) and Hu et al. (2020) also reported that supplementing broilers with antibiotic growth promoters (tylosin, neomycin sulfate, bacitracin, erythromycin, and oxytetracycline or virginiamycin) increased the abundance of Proteobacteria .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The bacteria of the Parasutterella genus were shown to positively correlate with the chronic inflammatory state and drove insulin resistance [ 27 ]. The abundance of Parasutterella remarkably increased in HFD-induced T2D mice and decreased after the treatment of novel antidiabetic monomers [ 28 ]. The Candidatus Soleaferrea genus was known to possess anti-inflammatory effects by secreting metabolites and intestinal homeostasis protection properties [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our data show that 5 genera were independent predictors of HOMA (an index of insulin resistance), 2 of them in a positive manner ( Candidatus soleaferrea and Peptoclostridium ) and 3 in a negative one ( uncultured Muribaculaceae, Eubacterium oxidoreducens group and Holdemania ). Different data have also reported the association between insulin resistance and the levels of these genera [ 14 , 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%